Building an intelligent map of a community health center: case study - Vivian Elizabeth Araujo; Ivani Bueno de Almeida Freitas; Giselda Quintana Marques (Online Brazilian Journal of Nursing, 2005)
This is a report about the experience of creating an intelligent map of IAPI`s Health Center/POA surroundings. Professional healthcare workers and nursing students did the project through active observation. Based on an established itinerary, the field observations involved the transcriptions of the collected information on maps with the usage of different colors and symbols. This experience allowed better knowledge of the region, its geophysics and population characteristics, as well as the risk factors in the area and the importance of this kind of instrument in public health units.